Shenfu injection provides protection for perinatal asphyxia in neonates (Bangladesh Journal of Pharmacology, 2016)
This study aimed to investigate the efficacy of shenfu injection for the protection of neonates with asphyxia. Eighty neonates with asphyxia were randomly divided into two groups, treatment group and control group (n=40). Both groups received interventions such as ventilation, oxygen, and circulation support. Treatment group was administrated with shenfu injection additionally. Serum levels of creatine kinase, alanine aminotransferase, aspartate aminotransferase, creatinine, and neuron-specific enolase were significantly lower but the oxygenation index was significantly higher in treatment group on day 7 and day 14. The neurobehavioral score was significantly higher in treatment group than in control group. On the 14th day, the survival rate of treatment group (77.5%) was higher than that of control group (55%). Shenfu injection could protect the function of the brain, heart, lung, liver and kidney by attenuating ischemia reperfusion after severe asphyxia resuscitation, improve neurobehavioral ability and increase the survival of neonates.